Pemenuhan Hak Restitusi Anak Korban Tindak Pidana Persetubuhan (Kasus Herry Wirawan) - Triono, Agus; Saputra, Dadang Herli (Universitas Sultan Ageng Tirtayasa, 2024)
Child victims of sexual intercourse are victims of criminal acts who experience losses that are not only material in nature, but also experience psychological suffering. Restitution is the payment of compensation that is charged to the perpetrators of a crime based on a court decision that has permanent legal force for material or immaterial losses. Restitution is also a form of protection for victims of sexual intercourse and is a form of law enforcement for perpetrators of sexual intercourse to pay restitution as a form of compensation for losses suffered by victims. The author takes a case study that occurred in Bandung, the case of intercourse by a teacher with female students. The judge sentenced the defendant to death and paid restitution to the victims as a form of compensation for the losses suffered by the female students. Providing restitution to victims of sexual intercourse is very important, because restitution will at least reduce the burden of losses experienced by victims of sexual intercourse.